2022
DOI: 10.1007/s10787-022-01001-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of Edaravone on clinical outcome of patients with severe COVID-19 admitted to ICU: a randomized clinical trial

Abstract: Cytokine storm is the most prominent hallmark in patients with coronavirus disease 2019 (COVID-19) that stimulates the free radical storm, both of which induce an overactive immune response during viral infection. We hypothesized that owning to its radical-scavenging and anti-inflammatory properties, Edaravone could reduce multi-organ injury, clinical complications, and mortality in severe COVID-19 cases. This single-center randomized clinical trial was accompanied in the intensive care units (ICUs) of the tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, edaravone exhibits the ability to safeguard organs against inflammation, radiation, and ischemia–reperfusion injury. 27 , 28 , 29 , 30 In animal models, pre‐treatment with edaravone has been shown to attenuate renal injury and histologic changes after contrast administration via increasing renal antioxidant capacity. 31 Correspondingly, in the present study, the administration of edaravone 1 h before contrast usage resulted in a decrease in the incidence of CIN, with only one patient experiencing CIN development compared to four patients in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, edaravone exhibits the ability to safeguard organs against inflammation, radiation, and ischemia–reperfusion injury. 27 , 28 , 29 , 30 In animal models, pre‐treatment with edaravone has been shown to attenuate renal injury and histologic changes after contrast administration via increasing renal antioxidant capacity. 31 Correspondingly, in the present study, the administration of edaravone 1 h before contrast usage resulted in a decrease in the incidence of CIN, with only one patient experiencing CIN development compared to four patients in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been done to examine the benefit of different medications that were allocated based on their mechanism of action to improve the outcomes of patients with COVID‐19. 18 Li and colleagues reported that lopinavir/ritonavir (LPV/r) or arbidol monotherapy exerted little benefit in enhancing the clinical outcomes of mild/moderate COVID‐19 patients. 19 In another randomized clinical trial in COVID‐19 patients with mild‐to‐moderate pneumonia, it has been shown that anakinra (a recombinant human IL‐1 receptor antagonist) could not enhance patients' outcomes and was not effective in reducing the need for non‐invasive or mechanical ventilation or death.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been done to examine the benefit of different medications that were allocated based on their mechanism of action to improve the outcomes of patients with COVID‐19 18 . Li and colleagues reported that lopinavir/ritonavir (LPV/r) or arbidol monotherapy exerted little benefit in enhancing the clinical outcomes of mild/moderate COVID‐19 patients 19 .…”
Section: Discussionmentioning
confidence: 99%